Tuning the circularly polarized luminescence in homoleptic and heteroleptic chiral CrIII complexes - Poncet, Maxime; Besnard, Céline; Guénée, Laure; Jiménez, Juan-Ramón; Piguet, Claude (Frontiers in Chemistry, 2024)
A series of highly emissive inert and chiral CrIII complexes displaying positive and negative circularly polarized luminescence (CPL) within the near-infrared (NIR) region at room temperature have been prepared and characterized to decipher the effect of ligand substitution on the photophysical properties, more specifically on the chiroptical properties. The helical homoleptic [Cr(dqp-R)2]3+ (dqp = 2,6-di(quinolin-8-yl)pyridine; R = Ph, ≡-Ph, DMA, ≡-DMA (DMA = N,N-dimethylaniline)) and heteroleptic [Cr(dqp)(L)]3+ (L = 4-methoxy-2,6-di(quinolin-8-yl)pyridine (dqp-OMe) or L = N2,N6-dimethyl-N2,N6-di(pyridin-2-yl)pyridine-2,6-diamine (ddpd)) molecular rubies were synthesized as racemic mixtures and then resolved and isolated into their respective pure PP and MM enantiomeric forms by chiral stationary phase HPLC. The corresponding enantiomers show two opposite polarized emission bands within the 700–780 nm range corresponding to the characteristic metal-centered Cr(2E’→4A2) and Cr(2T1’→4A2) transitions with large glum ranging from 0.14 to 0.20 for the former transition. In summary, this study reports the rational use of different ligands on CrIII and their effect on the chiroptical properties of the complexes.